Dissemination of Technical Assistance Information. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
This paper sets out a framework for streamlined and strengthened procedures for the wider dissemination of technical assistance-related information ("TA Information"). On the basis of this framework, management intends to issue guidelines to the staff setting forth these new procedures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Fund; PP; TA Information; TA Recipient; TA